Political economies of the Aegean Bronze Age papers from the Langford Conference, Florida State University, Tallahassee, 22-24 February 2007 - Langford Conference of the Department of Classics (2007 : Florida State University); Pullen, Daniel J., 1954-; ebrary, Inc. (Oxford : Oxford Books ; Oakville, Conn. : Distributed by David Brown, 2010)
"This volume brings together an international group of researchers to address how Mycenaean and Minoan states controlled the economy. The contributions, originally delivered at the 2007 Langford Conference at Florida State University, examine the political economies of state (and pre-state) entities within the Aegean Bronze Age, including the issues of: centralization and multiple scales of production, distribution, and consumption within a polity; importance of extraregional trade; craft specialization; the role of non-elite institutions, and the political economy before the emergence of the palaces. The contributors address these issues from an explicitly comparative perspective, both within and across Minoan and Mycenaean contexts. The conclusions reached in this volume shed new light on the essential differences between and among "Minoan" and "Mycenaean" states through their political economies"--Publisher's description.
Introduction: political economies of the Aegean Bronze Age / Daniel J. Pullen -- Beyond the peer: social interaction and political evolution in the Bronze age Aegean / William A. Parkinson -- Spirit of place: Minoan houses as major actors / Jan Driessen -- Making elites: political economy and elite culture(s) in middle Minoan Crete / Ilse Schoep -- From the kinship economy to the palatial economy: the Argolid in the second millennium BC / Sofia Voutsaki -- Political economies in ritual: a comparative study of the rise of the state in pre- and protopalatial Knossos and Phaistos / Joanne M.A. Murphy -- Reevaluating staple and wealth finance at Mycenaean Pylos / Dimitri Nakassis -- Seafaring in the Bronze Age Aegean: evidence and speculation / Cheryl A. Ward -- Between and beyond: political economy in non-palatial Mycenaean worlds / Thomas F. Tartaron -- Citadel and settlement: a developing economy at Mycenae, the case of Petsas House / Kim Shelton -- Living from pots? Ceramic perspectives on the economies of prepalatial Crete / Peter M. Day, Maria Relaki, and Simona Todaro -- Wedging clay: combining competing models of Mycenaean pottery industries / Michael L. Galaty -- Political economies in the Aegean Bronze Age: a response / James C. Wright.
Includes bibliographical references.
Electronic reproduction.
Keywords: Bronze age -- Aegean Sea Region -- Congresses; Minoans -- Congresses; Civilization, Mycenaean -- Congresses; Aegean Sea Region -- Economic conditions -- Congresses; Aegean Sea Region -- Politics and government -- Congresses; Aegean Sea Region -- Antiquities -- Congresses; Crete (Greece) -- Economic conditions -- Congresses; Crete (Greece) -- Politics and government -- Congresses; Crete (Greece) -- Antiquities -- Congresses; Electronic books